METHOD FOR ANALYSIS OF DIMENSIONAL CHANGE OF KNITTED PRODUCTS AFTER WASHING - G‘ulomov Xayotbek Xasanboy o’g‘li (American Journals Publishing, 2024)
This article is in accordance with ISO 3005, ISO 7771, ISO 3759, testing for dimensional change after washing, dry cleaning, soaking and steaming. It also includes learning how to make, mark and measure textiles and clothing.The method used in this article is described as applicable to fabrics, knitted fabrics and finished textiles.
Keywords: ISO 3005, ISO 7771, ISO 3759, ISO 139, knitted, measuring, dimensions